Assessing reward preference using operant behavior in male and female mice. - Rose-Marie Karlsson; Heather A Cameron (PLoS ONE)
Many different solid food pellets are available as reinforcers for rodents in operant behavior tests. Different reward formulations have not been compared, so it is unclear whether mice show strong preferences for different rewards and whether such preferences are consistent within or across sex and background strain. Here we show that mice have strong preferences for two balanced diet food rewards over sucrose pellets, and preference for one balanced diet pellet formulation over another, in a simultaneous choice test using a low effort fixed ratio operant test. All mice, of both sexes and both CD1 and C57 background strains, showed the same strong preferences among these three types of reinforcers. In contrast, flavorings added to the reward pellets had relatively small and more variable effects on preference. The preference for balanced diet pellets over sucrose pellets was seen also in the total numbers of rewards consumed in low effort tests with food pellets or only sucrose pellets available. However, progressive ratio testing showed that mice worked harder for sucrose pellets than for the preferred balanced diet pellets. These findings indicate that reinforcers with similar and very different preference profiles are readily available and that testing with different rewards can produce different, and sometimes unexpected, results.